Business continuity management systems implementation and certification to ISO 22301 - Estall, Hilary (BCS, The Chartered Institute for IT, 2012)
Annotation
Includes bibliographical references and index. - Online resource; title from .pdf information screen (Ebsco, viewed October 30, 2012)
Keywords: Crisis management; Emergency management; Business planning; Gestion de crise; Business applications; Business strategy; Business mathematics & systems; TECHNOLOGY & ENGINEERING; Emergency Management; Enterprise software; Economic systems & structures